An Observational Retrospective Cohort Trial on 4,828 IVF Cycles Evaluating Different Low Prognosis Patients Following the POSEIDON Criteria - Levi-Setti, Paolo Emanuele; Zerbetto, Irene; Baggiani, Annamaria; Zannoni, Elena; Sacchi, Laura; Smeraldi, Antonella; Morenghi, Emanuela; De Cesare, Raffaella; Drovanti, Alessandra; Santi, Daniele (Frontiers in Endocrinology, 2019)
Objective: To study the actual controlled ovarian stimulation (COS) management in women with suboptimal response, comparing clinical outcomes to the gonadotropins consume, considering potential role of luteinizing hormone (LH) addition to follicle-stimulating hormone (FSH). Design: Monocentric, observational, retrospective, real-world, clinical trial on fresh intra-cytoplasmic sperm injection (ICSI) cycles retrieving from 1 to 9 oocytes, performed at Humanitas Fertility Center from January 1st, 2012 to December 31st, 2015. Methods: COS protocols provided gonadotropin releasing-hormone (GnRH) agonist long, flare-up, short and antagonist. Both recombinant and urinary FSH were used for COS and LH was added according to the clinical practice. ICSI outcomes considered were: gonadotropins dosages; total, mature, injected and frozen oocytes; cumulative, transferred and frozen embryos; implantation rate; pregnancy, delivery and miscarriage rates. Outcomes were compared according to the gonadotropin regimen used during COS. Results: Our cohort showed 20.8% of low responders, defined as 1-3 oocytes retrieved and 79.2% of “suboptimal” responders, defined as 4-9 oocytes retrieved. According to recent POSEIDON stratification, cycles were divided in group 1 (6.9%), 2 (19.8%), 3 (11.7%) and 4 (61.5%). The cohort was divided in 3 groups, according to the gonadotropin’s regimen. Women treated with FSH plus LH showed worst prognostic factors, in terms of age, basal FSH, AMH and AFC. This difference was evident in suboptimal responders, whereas only AMH and AFC were different among treatment groups in low responders. Although a different result, in terms of oocytes and embryos detected, major ICSI outcomes (i.e. pregnancy and delivery rates) were similar among groups of COS treatment. Outcomes were significantly different among Poseidon groups. Outcomes rates were significantly higher in Poseidon group1 and progressively declined in other POSEIDON groups, reaching the worst percentage in group 4. Conclusions: In clinical practice, women with worst prognosis factors are generally treated with a combination of LH and FSH. Despite low prognosis women showed a reduced number of oocytes retrieved, the final ICSI outcome, in terms of pregnancy, is similarly among treatment group. This result suggests that the LH addition to FSH during COS could improve the quality of oocytes retrieved, balancing those differences that are evident at baseline.